MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR SEJARAH INDONESIA I MELALUI MODEL CTL BERBANTUAN BAHAN AJAR - Syahrul Amar; Abdul Rasyad; Andi Sulastri (Universitas Hamzanwadi, 2014)
Problems historical learning process is the low activity and student learning outcomes. This is due to lack of appropriate learning model in learning. Learning model that can be used to overcome this problem is the model CTL-aided instructional materials. Contextual Learning (CTL) presents the events of the past into the real world who directly witnessed the student. This study aims to improve the activity and learning outcomes through CTL model-aided instructional materials Indonesian History course I .. This research is a class action that includes planning, implementation, observation / evaluation and reflection. The research activities conducted on the activities and learning outcomes and student responses to deploy lecture. The subject of the first semester students study History Education Studies Program. Activity data were collected using the observation sheet. Data were collected using a test of learning outcomes. Student response data on the implementation of the course through observation and interviews. The results showed activity in the learning cycle I had an average score of 5.27 with a fairly active category. The second cycle of increased activity learning with an average score of 7.5 with Active category. Results of study subjects Indonesian History I through CTL Model-aided instructional materials increased from the first cycle to the second cycle where the average value of learning outcomes in the first cycle is 63, 77 (enough) and the second cycle of the average value increased by 73.40 (high). Student response to the application of the model identified CTL strongly agree.Keywords: CTL, Instructional Materials, Activity, Learning Outcomes